OUTCOMES OF OPEN THORACIC SURGICAL DECORTICATION IN PATIENTS WITH TUBERCULOUS EMPYEMA - Aslam, Tahir; Bilal, Amer; Ahmed, Manzoor; Abid, Mohammad; Baseer, Abdul; Baloch, Khurshid Ahmed; Ali, Fawad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To analyze the outcome of open surgical decortication of tuberculous empyema patients at their late presentation.Study Design: Cross sectional study.Place and Duration of Study: Patients (n = 128) with tuberculous empyema were subjected to decortication for one and half year starting from July 2017 to December 2018. Pre, intra, and post-operative characteristics of all patients were studied thoroughly with a 6-month follow up evaluation of the surgical outcomes. Results: Preoperative conditions were as follows:  6.25% patient had Broncho pleural fistula, 90.9% patients were diagnosed with cough, 34.7 with night sweating, 64.2% chest pain and 79.6% chest tightness. Decortication was performed in all cases, with debridement of necrotic tissue and repair of air leaks in some patients. 70 (54.7%) patients went through right side decortication, whereas 56 (43.7%) patients went through left sided decortication and 2 (1.56%) patients had bilateral. Mortality was 2 (1.56%), 1 patient died of septicemia while 1 of pulmonary embolism. Whereas morbidity was 9 (7%), 3 patients had wound infection, 4 had incomplete lung expansion, 1 patient each had prolonged air leak and post-operative bleeding.Conclusions: Delayed referral for surgery causes irreversible changes in the lung, and prolonged disease condition, which causes increased thickness of the pleura and injury to the underlying lung with a delayed recovery. Open decortication gives satisfactory results.